Technological competitiveness of the EU member states in the era of the fourth industrial revolution - Weresa, Marzenna Anna (Economics and Business Review, 2019)
The aim of this paper is to investigate the implications of the fourth industrialrevolution for technological competitiveness, its definition and measurement methods.An empirical part is aimed at identifying comparative advantages of the EuropeanUnion in digital technologies. Recently new approaches have appeared to measuredigital competitiveness, however they use a broad definition of competitiveness thatencompasses not only technological factors but also the macroeconomic and institutionalenvironment (IMD, 2017; WEF, 2018). There is still a limited number of studiesfocused on the technological dimension of competitiveness in digital technologies. Thispaper fills the gap by developing a conceptual framework based on patent indicators,i.e. Patent Share and Revealed Technological Advantage indices. It allows a consistentanalysis of the comparative advantages of the EU member states in digital technologiesto be conducted. The results confirm a huge diversity within the EU in terms ofdigital technologies, their global impact and comparative advantages.